Fractionation and reconstitution of factors required for accurate transcription of mammalian ribosomal RNA genes: identification of a species-dependent initiation factor. - Mishima, Y (1982)
Mouse and human cell extracts (S100) can support an accurate and efficient transcription initiation on homologous ribosomal RNA gene (rDNA) templates. The cell extracts were fractionated with the aid of a phosphocellulose column into four fractions (termed A, B, C and D), including one containing a major part of the RNA polymerase I activity. Various reconstitution experiments indicate that fraction D is an absolute requirement for the correct and efficient transcription initiation by RNA polymerase I on both mouse and human genes. Fraction B effectively suppresses random initiation on these templates. Fraction A appears to further enhance the transcription which takes place with fractions C and D. Although fractions A, B and C are interchangeable between mouse and human extracts, fraction D is not; i.e. initiation of transcription required the presence of a homologous fraction D for both templates. The factor(s) in fraction D, however, is not literally species-specific, since mouse D fraction is capable of supporting accurate transcription initiation on a rat rDNA template in the presence of all the other fractions from human cell extract under the conditions where human D fraction is unable to support it. We conclude from these experiments that a species-dependent factor in fraction D plays an important role in the initiation of rDNA transcription in each animal species.